Sistem Pengukuran Kinerja dan Kinerja Pembiayaan bagi Hasil Perbankan Syariah di Indonesia - Trishananto, Yudha (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2016)
This study aims to examine the role of Management Control System (MCS),attitude to risk and organizational learning to improve the performance ofprofit and loss of sharing defrayal. MCS concept used in this study is diagnostic, interactive and dynamic performance measurement system (PMS). Performance of defrayal of profit and revenue sharing is operationalized into the quantity and quality of defrayal. This study uses a survey by branches of Islamic banks in Indonesia. A total of 99 questionnaires were returned. It is proven that interactive use of PMS has a positive effect on the attitude towards risk and learning organization. This study shows that the resource-based view further elucidate the role of the PMS improves performance compared with agency theory. Practically, this study demonstrates the role of PMS as a system to control the behavior of managers in improving the performance of Islamic banks profit and loss of sharing defrayal